Intermediate annealing of pure aluminum during cyclic equal channel angular pressings - Chang, JY; Shan, A (KLUWER ACADEMIC PUBL, 2003)
Intermediate heat treatment was employed to anneal pure Al samples subjected to cyclic Equal Channel Angular (ECA) pressing in order to investigate the microstructural change and tensile properties of as-pressed and annealed samples. As-pressed samples were annealed at 200 degreesC for 1 hr after 2 and 4 passages. Some annealed samples were pressed further to compare the changes in the properties of pure Al with the same equivalent strain induced by cyclic ECAP but having different thermal history. Intermediate annealing in the cyclic repetitive ECA pressing appears to be an effective method to form an equiaxed, fine-grained structure with high misorientation angle. It decreases the aspect ratio of subgrains while keeping the grains size unchanged. Annealing followed by further pressing results in an increase in the aspect ratio but small decrease in the grain size. It is speculated that recrystallization of ECA pressed aluminum is responsible for the significant increase in the misorientation angle. (C) 2003 Kluwer Academic Publishers.
Keywords: SUBMICROMETER GRAIN-SIZE; AL-MG ALLOY; MICROSTRUCTURE; DEFORMATION